Analisis Kriminologis Terhadap Kasus Kawin Tangkap Pada Masyarakat Sumba Barat Daya (Studi Kasus di Polres Sumba Barat Daya) - Cornelis Derry Wonderson kalli; Karolus Kopong Medan; Debby F Ng Fallo (Artemis Law Journal, 2026)
Capture marriage is a form of marriage in which a woman is kidnapped or forcibly captured to be made a wife. The capture marriage tradition is one of the customary laws of the Sumba community, East Nusa Tenggara (NTT). The purpose of this study was to determine (1) the factors causing the occurrence of capture marriage cases in the Southwest Sumba community, and (2) efforts to resolve capture marriage cases in the Southwest Sumba community. This type of research is empirical legal research or empirical juridical legal research. This approach uses a qualitative approach, namely research that intends to understand the phenomenon of what is experienced by the research subject. The causal factors come from external factors, namely factors originating from outside the perpetrator and internal factors, namely those originating from within the perpetrator. Settlement efforts use two settlement efforts, namely penal efforts or settlement using criminal law and non-penal efforts or settlement efforts outside of criminal law.